Is the Composition of the Pentateuch Too Complex to Be Taught? - Schmid, Konrad (Teaching theology and religion, 2025)
The composition of the Pentateuch is a contested issue. Current theories are best taught by explaining the dynamics in the history of research that led to the main theories and their critiques that are currently dominating the scholarly discussion.